Turbulent flow: Innovations in viscosity analysis - Chaves Dos Santos, Romulo Damasclin (Revista de Matemática da UFOP, 2024)
The mathematical analysis outlined in this study establishes a foundational framework for exploring the regularity of the Navier-Stokes equations. Within this scope, our research represents a significant advancement in utilizing the Smagorinsky model in conjunction with Large-Eddy Simulation (LES), culminating in the formulation of a novel theorem rooted in Banach and Sobolev Spaces. While the explicit construction of an anisotropic viscosity model is beyond the current scope, this theorem lays the groundwork for its development. By employing sophisticated mathematical analysis, our work facilitates a comprehensive grasp of the complexities surrounding the regularity challenges inherent in the Navier-Stokes equations.